Identifikasi Efektivitas Daun Pedada (Sonneratia Caseolaris) Sebagai Antimikroba dan Potensinya dalam Pengobatan Tradisional - Nayla Fazilla Nadin; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Pedada leaves (Sonneratia caseolaris), a type of mangrove plant that grows in tropical and subtropical coastal areas, have high ecological and pharmacological value. In addition to functioning as coastal protection from abrasion and seawater intrusion, this plant is also known to contain various secondary metabolite compounds such as flavonoids, tannins, saponins, and alkaloids. These compounds have been widely reported to have important biological activities, one of which is as an antimicrobial agent. This study aims to identify the effectiveness of pedada leaf ethanol extract in inhibiting the growth of pathogenic microorganisms, especially bacteria that cause infections. The extraction process was carried out using 96% ethanol solvent through the maceration method, namely soaking the material in the solvent for a certain time to optimally obtain active compounds. The obtained extract was then tested for its antimicrobial activity using the disc diffusion method against test bacteria, both Gram-positive and Gram-negative. The inhibition zone formed around the disc was measured as an indicator of the antibacterial effectiveness of the extract. The results showed that pedada leaf extract was able to produce inhibition zones with varying diameters depending on the concentration used. The higher the extract concentration, the larger the diameter of the inhibition zone formed. This indicates a positive relationship between extract concentration and its antibacterial strength. This activity is believed to originate from the ability of compounds such as flavonoids and tannins to damage bacterial cell walls or disrupt microbial metabolic processes. This study provides initial evidence that pedada leaves have potential as an environmentally friendly and sustainable source of natural antibacterials. This potential is highly relevant in efforts to develop alternative antibacterial materials based on local plants, especially amidst increasing bacterial resistance to synthetic antibiotics.